2013
DOI: 10.1371/journal.pone.0062950
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Retinoic Acid Receptor Beta2(RARβ2) Methylation Status and Prostate Cancer Risk: A Systematic Review and Meta-Analysis

Abstract: The retinoic acid receptor beta2(RARβ2) is a type of nuclear receptor that is activated by both all-trans retinoic acid and 9-cis retinoic acid, which has been shown to function as a tumor suppressor gene in different types of human tumors. Previous reports demonstrated that the frequency of RARβ2 methylation was significantly higher in prostate cancer patients compared with controls, but the relationship between RARβ2 promoter methylation and pathological stage or Gleason score of prostate cancer remained con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The methylation of CpGs in the P2 promoter sequence of RARB is usually addressed to epigenetically influence its transcription [3,19,28]. This region (containing an Sp1 element) is amplified by MSP and entails a major and appropriate number of CpGs which could be analyzed by the methylationspecific and nonspecific primers represented in Table 1 [3,12,28,29].…”
Section: Dietary Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The methylation of CpGs in the P2 promoter sequence of RARB is usually addressed to epigenetically influence its transcription [3,19,28]. This region (containing an Sp1 element) is amplified by MSP and entails a major and appropriate number of CpGs which could be analyzed by the methylationspecific and nonspecific primers represented in Table 1 [3,12,28,29].…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…There is also convincing evidence of tissue and gene specificity of hypermethylated genes in association with plasma folate in specific malignancies, such as colorectal cancer (CRC) [9,13,18]. The preferential modulation of regional methylation through which dietary methyl donor components can selectively influence the gene expression remains to be illuminated [9,19].…”
Section: Introductionmentioning
confidence: 99%
“…AR signaling, central to prostate cancer progression [77], is known to be epigenetically regulated [78]. The tumor suppressor RARβ2 , similar to its hypermethylation in breast cancer [54, 79], cervical cancer [53] and leukemia [80], is significantly more hypermethylated in prostate cancer patients, and correlates with increased tumor risk [81]. Role of SPARC has been investigated in multiple cancer models [82] and its function largely depends on whether it is produced by cancer cells or the stromal cells in the tumor microenvironment [82].…”
Section: Epigenetics In Cancer Health Disparitiesmentioning
confidence: 99%
“…These findings suggest that epigenetic silencing of miR-9 loci constitutes an important event in breast carcinogenesis. In an study, Xu et al (2013) found that DNMT1 expression, which is aberrantly upregulated in breast cancer and its overexpression is responsible for the hypermethylation of miR-148a and miR-152 promoters, and is inversely correlated with the expression levels of miR-148a/152 in breast cancer tissues; suggesting a negative feedback regulatory loop between miR-148a/152 and DNMT1 in breast cancer (Xu et al 2013). Interestingly, upon treatment of the breast cancer cells with a DNA demethylating agent, reduced tumor growth and inhibition of metastasis were also documented through the reactivation of miR-148.…”
Section: Breast Cancermentioning
confidence: 99%